Autologous and Heterologous Minor and Major Bone Regeneration with Platelet-Derived Growth Factors - Gianna Dipalma; Angelo Michele Inchingolo; Valeria Colonna; Pierluigi Marotti; Claudio Carone; Laura Ferrante; Francesco Inchingolo; Andrea Palermo; Alessio Danilo Inchingolo (Journal of Functional Biomaterials)
Aim: This review aims to explore the clinical applications, biological mechanisms, and potential benefits of concentrated growth factors (CGFs), autologous materials, and xenografts in bone regeneration, particularly in dental treatments such as alveolar ridge preservation, mandibular osteonecrosis, and peri-implantitis. Materials and Methods. A systematic literature search was conducted using databases like PubMed, Scopus, and Web of Science, with keywords such as “bone regeneration” and “CGF” from 2014 to 2024. Only English-language clinical studies involving human subjects were included. A total of 10 studies were selected for qualitative analysis. Data were processed through multiple stages, including title and abstract screening and full-text evaluation. Conclusion: The findings of the reviewed studies underscore the potential of the CGF in enhancing bone regeneration through stimulating cell proliferation, angiogenesis, and extracellular matrix mineralization. Autologous materials have also demonstrated promising results due to their biocompatibility and capacity for seamless integration with natural bone tissue. When combined with xenografts, these materials show synergistic effects in improving bone quantity and quality, which are crucial for dental implant success. Future research should focus on direct comparisons of different techniques, the optimization of protocols, and broader applications beyond dental medicine. The integration of CGFs and autologous materials into routine clinical practice represents a significant advancement in regenerative dental medicine, with the potential for improved patient outcomes and satisfaction.